6'-O-Lactose Ester Surfactants as an Innovative Opportunity in the Pharmaceutical Field: From Synthetic Methods to Biological Applications - Michele Verboni; Simone Lucarini; Andrea Duranti (MDPI AG, 2021)
Glycolipid surfactants are biocompatible and biodegradable compounds characterized by potential applications in various sectors including pharmaceuticals, cosmetics, agriculture, and food production. A specific overview regarding synthetic methodologies and properties of 6'-lactose-based surfactants is presented herein, particularly all the synthetic approaches to this class of lactose esters, such as enzymatic and traditional organic syntheses. Moreover, detailed descriptions of physicochemical data and biocompatibility properties of these molecules, that is, surface tension, critical micelle concentration, emulsifying ability, foaming, particle size distribution, biocompatibility, and safety, are described. Biological applications with a focus on permeability enhancing, antimicrobial activity, and antibiofilm properties of 6'-lactose-based esters are also reported.